Autonomic effects of selegiline: possible cardiovascular toxicity in Parkinson's disease. Issue 2 (1st August 1997) - Churchyard, A; Mathias, C J; Boonkongchuen, P; Lees, A J
Abstract : OBJECTIVES: The United Kingdom Parkinson's Disease Research Group (UKPDRG) trial found an increased mortality in patients with Parkinson's disease randomised to receive selegiline (10 mg/day) and levodopa compared with those taking levodopa alone. Unwanted effects of selegiline on cardiovascular regulation have been investigated as a potential cause for the unexpected mortality finding of the UKPDRG trial. METHODS: The cardiovascular responses to a range of physiological stimuli, including standing and head up tilt, were studied in patients with Parkinson's disease receiving levodopa alone and a matched group on levodopa and selegiline. RESULTS: Head up tilt caused selective and often severe orthostatic hypotension in nine of 16 patients taking selegiline and levodopa, but was without effect on nine patients receiving levodopa alone. Two patients taking selegiline lost consciousness with unrecordable blood pressures and a further four had severe symptomatic hypotension. The normal protective rises in heart rate and plasma noradrenaline were impaired. The abnormal response to head up tilt was reversed by discontinuation of selegiline. Drug withdrawal caused a pronounced deterioration in motor function in 13 of the 16 patients taking selegiline. CONCLUSION: Therapy with selegiline and levodopa in combination may be associated with severe orthostatic hypotension not attributable to levodopa alone. Selegiline also has pronounced symptomatic motor effects in advanced Parkinson's disease. The possibilities that these cardiovascular and motor findings might be due either to non-selective inhibition of monoamine oxidase or to amphetamine and met-amphetamine are discussed.